Об энергии магнито-статического поля - Буданов, В.Е.; Буданов, О.В.; Суслов, Н.Н. (Проблемы машиностроения, 2016)
Сомнения в достоверности знака «плюс», стоящего перед слагаемым для плотности энергии магнитостатического поля в формуле Пойнтинга, следует, например, из такого факта. Если взять два одинаковых точечных заряда, равномерно движущихся с одинаковыми скоростями, то в общем случае на заряды будут действовать силы электрического отталкивания, направленные вдоль прямой, их соединяющей. Но вдоль этой же линии будут действовать составляющие сил магнитного притяжения, так что для сближения зарядов будет затрачена работа, меньшая той, когда бы магнитное взаимодействие отсутствовало. И этот факт обусловливает выдвижение гипотезы об отрицательности энергии магнитостатического поля. С использованием принципа виртуальной работы рассмотрено силовое воздействие статических электрического и магнитного полей, локализованных в равномерно движущемся эллипсоидальном слое на синхронно с ним движущийся вне слоя точечный заряд. Показано, что во избежание нарушения принципа сохранения энергии (равно как и принципа относительности) статическое магнитное поле должно обладать отрицательной энергией. Certain facts cast some doubt upon the ‘plus’ sign of the term for the energy flux of a magnetostatic field in the Poynting formula. To cite an example, consider two equal point charges moving uniformly with equal velocities. Generally the electric repulsive forces act on the charges, being directed along the line connecting them. At the same time, components of the magnetic attracting forces act along the same line, and so the work required to bring the charges together is smaller than if magnetic interaction were absent. This fact motivates the hypothesis that the energy of a magnetostatic field is negative. A force action of electrostatic and magnetostatic fields localized in a uniformly moving ellipsoidal layer on a point charge moving synchronously outside the layer is discussed using the virtual work principle. It is shown that in order to avoid violation of the principle of the conservation of energy (as well as of the relativity principle) the energy of a magnetostatic field must be negative. In our proof we are dealing with the energy of ‘co-occurrence’ of two simplest objects of classical electrodynamics – the point charges qT and qC. The entire space around the charge qC may be considered as subdivided into spherical (or ellipsoidal) layers; for each of these layers the theorem on negativity of the energy of a magnetostatic field is proved.